Qualidade de preenchimento e retratabilidade de cimentos à base de silicato de cálcio com diferentes formulações - Lena, Isabella Marian (2024)
The quality of endodontic obturation and efficient removal of the filling material are essential concerns during endodontic treatment and retreatment, respectively. This thesis consists in two scientific articles. Article 1 aimed to evaluate the percentage of voids and gaps in oval root canals filled with two calcium silicate-based endodontic sealers with different formulations, using micro-computed tomography (micro-CT) imaging. Eighty-four mandibular anterior teeth were selected and prepared with Reciproc R25 nickel-titanium reciprocating instruments. The teeth were then divided into two groups based on the sealer used: premixed (BCS - Bio-C Sealer) or powder-liquid (BRR - BioRoot RCS). After obturation using the single-cone technique, new micro-CT scans were performed. The percentage of voids and gaps in the apical, middle, and cervical thirds of the root canal was calculated using CTan software. Additionally, the surface morphology of the materials was evaluated by scanning electron microscopy (SEM). Mann-Whitney and Friedman tests were employed for statistical analysis (α = 5). BCS showed significantly lower percentages of total voids and gaps compared to BRR. Regarding the thirds, BRR exhibited the lowest percentage of marginal gaps in the cervical third. SEM analysis revealed that BCS has a homogeneous and uniform surface, while BRR exhibits a more irregular and porous surface. Article 2 aimed to evaluate the effectiveness of Flatsonic and EasyClean as complementary techniques in retreatment of oval root canals obturated with calcium silicate-based sealers with different formulations, using micro-CT imaging. The same 84 mandibular anterior teeth were used. As described, obturation was performed using BCS (n = 42) or BRR (n = 42). Initial removal of the filling material was performed with Reciproc R25 file, and apical enlargement with R40. Afterwards, Flatsonic instruments (n = 21) or EasyClean instruments (n = 21) were applied in each group. The percentage of residual filling material was evaluated by micro-CT. Apical extrusion of debris and operative time for retreatment were also assessed. Data were subjected to T, paired T, ANOVA and Mann-Whitney tests (α = 5). There were no significant differences between sealers (after R40 and after supplementary technique) and between root thirds. Both supplementary techniques significantly reduced the amount of remaining filling material, however Flatsonic resulted in less residual obturation material compared to EasyClean. However, Flatsonic induced more debris extrusion than EasyClean. The operative time was significantly longer for canals filled with BRR compared to BCS. In conclusion, the powder-liquid formulation had a negative impact on the quality of obturation of oval root canals, favoring the formation of voids and gaps. The use of Flatsonic ultrasonic tip promoted greater removal of residual obturation material, although it also favored apical extrusion of debris with the BRR sealer.